On the idea of an ‘ecological grammar’ of verbal discourse from a humancentered perspective - Wąsik, Elżbieta (Scripta Neophilologica Posnaniensia, 2018)
On the idea of an ‘ecological grammar’ of verbal discourse from a humancentered perspective